Study of physicochemical parameters and wetland water quality assessment by using Shannon’s entropy - Kunwar Raghvendra Singh; Rahul Dutta; Ajay S. Kalamdhad; Bimlesh Kumar (Applied Water Science, 2022)
Abstract In water quality monitoring programs, optimization between information craved and information collected involves scrupulous judgment making processes and management approaches. The present study explores the few essential aspects of water quality monitoring program considering Shannon’s entropy with case studies on a few lakes and wetlands in North Guwahati, Assam (India). Firstly, the loss of information by traditional water quality indices (WQIs) has been addressed by the use of entropy weighted WQIs (EWQIs) which takes into account the randomness of data sets removing error through subjective judgments of experts in assigning parameter weights. This concept was extended to the quantification of heavy metals. The concept of multi-criteria decision-making methods (MCDMs) such as TOPSIS was introduced which utilize entropy weights and rough set theory to give a reliable and unbiased description of overall pollution levels of each sampling location. This study will be of great help to various agencies which take care of the water supply and water pollution control since this forms a significant tool for easy understanding and thereby making their applicability uncomplicated.